Identification of bilinear material models of nonlinear beams on nonlinear foundation - Kaliszky, Sándor; Popper, György; Lógó, János; Károlyi, György (Computer Assisted Methods in Engineering and Science, 1996)
In the analysis of the problem the beam is modelled by hinge elements connected together by rigid bars while the foundation is replaced by spring elements supporting the hinges. The nonlinear behaviour of the beam and the foundation is described by specially formulated bilinear material models. The characteristics of these models are considered to be unknown but, on the other hand, the deflections of certain points of the beam are given. The goal of the investigation is to determine the best values of the material characteristics by the use of a mixed variational principle based on the bilinear material model and by the application of the identification methods. The problem is stated in the form of constrained, nonsmooth, nonlinear mathematical programming problem, and the identification is equivalent to finding the minima of a non-linear, multivariable functional. The application is illustrated by the solution of an example.